Empowerment in Recording Financial Statements with a Simple Accounting Model for Local Fish Farming MSMEs in Boyolangu District, Tulungagung Regency - Siti Itsna Syamsiyah; Muhamad Agus Alfiyan Nur Ahmada; Ning Wijayanti; Faisal Muchlis; Muhammad Idris Al Satria; Binti Nur Asiyah (PT FORMOSA CENDEKIA GLOBAL, 2025)
This activity aims to train the ability of MSME actors, especially local fish farmers in Boyolangu District, to organize financial records independently and introduce the preparation of profit and loss statements as part of simple financial reports. The targets of the service activities to farmers were 15 MSMEs. During the implementation, one of the main obstacles faced was the lack of initial knowledge of the participants regarding financial records and the assumption that accounting is complicated and less relevant to small businesses. The results of this service activity showed an increase in participants' understanding of the importance of structured financial records. Participants began to realize that financial reports can help them understand the financial condition of the business, estimate profits earned, and manage costs more wisely. In addition, this training also contributed to the creation of better business management, which is expected to encourage the growth and sustainability of fish farming businesses in the long term.